Australia's 2019–20 mega‐fires are associated with lower occupancy of a rainforest‐dependent bat. (24th June 2022) - Law, B. S.; Madani, G.; Lloyd, A.; Gonsalves, L.; Hall, L.; Sujaraj, A.; Brassil, T.; Turbill, C.
Abstract: Mega‐fires in the Australian summer of 2019–20 resulted in the largest ever documented forest fire extent. These fires impacted many species, but individual responses remain poorly known, making assessments of their conservation status and ongoing threats uncertain. We assessed the influence of the 2019–20 mega‐fires on habitat occupancy in the golden‐tipped bat Phoniscus papuensis, a specialist which roosts in suspended birds' nests and occurs in relictual Gondwanan rainforest not typically exposed to fire. We used trapping and accounted for nightly detection probability (lower detection with increasing rainfall) to estimate site occupancy. Occupancy increased with the local (1 km buffer surrounding each site) extent of rainforest, gullies and unburnt forest. The model predicted a strong negative effect of fire in the surrounding buffer, with occupancy reduced from >90% at sites with suitable habitat (extensive rainforest and gully systems) surrounded by unburnt forest to 20% when the entire surrounding area was burnt (regardless of severity). Gully rainforest sites surrounded by a mixture of burnt and unburnt forest were modelled to have intermediate occupancy values. On average, fire severity mapping revealed that 22% of rainforest in the 1 km buffer surrounding our burnt sites was unburnt, 61% had a low severity burn, while 17% experienced a high severity burn. The lower occupancy of P. papuensis in burnt rainforest was associated with a reduction in the abundance of suspended bird nests, a critical resource used for day‐roosting. Our results quantify the effects of extreme fire events on animal populations in rainforest that is normally unaffected by fire. The large extent of rainforest burnt during the 2019–20 Australian season of 'mega‐fires' and its strong negative effect on occupancy highlights the vulnerability of animal species reliant on fire‐sensitive habitat to a climate‐change driven increase in such extreme fire events. Abstract : Mega‐fires in the Australian summer of 2019‐20 resulted in the largest ever documented forest fire extent. We assessed the influence of the 2019‐20 mega‐fires on habitat occupancy of the golden‐tipped bat Phoniscus papuensis, a specialist which roosts in suspended birds' nests and occurs in Gondwanan rainforest not typically exposed to fire. There was a strong negative effect of fire in the surrounding neighbourhood on occupancy, and burnt rainforest was associated with a reduction in the abundance of suspended bird nests, a critical resource used for day‐roosting. Photo credit: George Madani